PENGARUH KOMITMEN ORGANISASI DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI DINAS KESEHATAN KABUPATEN LEBAK - Wildan Wildan; Ridho Rahmatullah (The Asia Pacific Journal Of Management Studies, 2020)
This study aims to examine the effect of organizational commitment and organizational climate on employee performance. The sampling technique used was saturated sampling with 72 respondents consisting of Lebak District Health Office Staff. Data collection is done by using a questionnaire to obtain data. Development of instruments through a variable indicator framework and testing instruments, as well as testing reliability and validity. The results showed that: (1) organizational commitment had a positive and significant direct effect on employee performance, (2) organizational climate had a positive and significant effect on employee performance and (3) organizational commitment had a positive and significant effect on organizational climate.